Students' Mathematical Literacy in Solving Contextual Problems: A Review of the Perceived of Logical Mathematical Intelligence - Dwi Aldi Hidayatulloh; Muhammad Zia Alghar; Muhammad Rizal Usman (Jurnal Inovasi Matematika, 2025)
Contextual problems play an important role as a medium for students to apply mathematical concepts. However, many students still have difficulty in understanding and interpreting the problem. Therefore, this study aims to describe the perceived of students' logical mathematical intelligence in solving contextual problems based on the mathematical literacy process. This study is a descriptive qualitative study. The research was conducted at Batu City Junior High School with 31 respondents. There were three research subjects representing the level of perceived of logical mathematical intelligence. The research instruments consisted of a questionnaire on the perceived of logical mathematical intelligence, a logical mathematical intelligence test, and an interview guideline. The data obtained were analyzed using the triangulation method. The results of the study showed that students' mathematical literacy with high perceived of logical mathematical intelligence met the employ, interpret and some formulate indicators. Then the mathematical literacy of students with moderate perceived of logical mathematical intelligence met the formulate, employ and some interpret indicators. In addition, the mathematical literacy of students with low perceived of logical mathematical intelligence only met some of the formulate and employ indicators. The findings of this study contribute to providing information and reflection materials for teachers in planning learning as an effort to improve mathematical literacy based on the perceived of students' logical mathematical intelligence.